PSI-Based Time Series Analysis Exploiting Copernicus SAR Images for Monitoring Kouris Dam in Cyprus - Alatza, Stavroula; Tzouvaras, Marios; Loupasakis, Constantinos; Fotiou, Kyriaki; Kontoes, Charalampos; Hadjimitsis, Diofantos G. (My University, 2024)
Kouris dam is the main water reservoir in Cyprus, located in Limassol, transferring water from the western part of Troodos mountains to the eastern part of the island, both for domestic and irrigation use. It is a 113 m high zoned earthfill dam with a central clay core. Since its construction, in 1988, it has overflown three times in 2004, 2012 and 2020. Therefore, the need for its continuous inspection is of great importance for safety reasons. For the detection of surface deformation in Kouris dam, the Persistent Scatterers Interferometry technique was applied on 167 Sentinel-1 images from 2015 to 2023. The InSAR time-series processing revealed small-scale displacements on the downstream slope of the dam with a maximum rate of -5mm/y. The LOS displacements were validated by geodetic measurements, provided by the Water Development Department of Cyprus. This can serve as a valuable tool for risk assessment and mitigation.
Keywords: dam monitoring; remote sensing; risk mitigation; persistent scatterers interferometry; Kouris dam